High Expression of Three-Gene Signature Improves Prediction of Relapse-Free Survival in Estrogen Receptor-Positive and Node-Positive Breast Tumors. Issue 10 (January 2015) - Thakkar, Arvind; Raj, Hemanth; Ravishankar,; Muthuvelan, Bhaskaran; Balakrishnan, Arun; Padigaru, Muralidhara
The objective of the present study was to validate prognostic gene signature for estrogen receptor alpha-positive (ERα+) and lymph node (+) breast cancer for improved selection of patients for adjuvant therapy In our previous study, we identified a group of seven genes ( GATA3, NTN4, SLC7A8, ENPP1, MLPH, LAMB2, and PLAT) that show elevated messenger RNA (mRNA) expression levels in ERα (+) breast cancer patient samples. The prognostic values of these genes were evaluated using gene expression data from three public data sets of breast cancer patients ( n = 395). Analysis of ERα (+) breast cancer cohort ( n = 195) showed high expression of GATA3, NTN4, and MLPH genes significantly associated with longer relapse-free survival (RFS). Next cohort of ERα (+) and node (+) samples ( n = 109) revealed high mRNA expression of GATA3, SLC7A8, and MLPH significantly associated with longer RFS. Multivariate analysis of combined three-gene signature for ERα (+) cohort, and ERα (+) and node (+) cohorts showed better hazard ratio than individual genes. The validated three-gene signature sets for ERα (+) cohort, and ERα (+) and node (+) cohort may have potential clinical utility since they demonstrated predictive and prognostic ability in three independent public data sets.